Somatic and population adaptations of Polysarcus denticauda (Orthoptera) in extreme altitudes - Kaňuch, Peter; Krištín, Anton (Entomologica Fennica, 2009)
Altitudinal preferences, somatic and population adaptations in different ecological conditions were analysed in flightless bush-cricket species Polysarcus denticauda (Charpentier, 1825). Altitudinal analysis was performed in GIS software (more than 60 sites in Slovakia, Central Europe). Seasonal occurrence and population density were recorded in selected sites. To compare differences, absolute values of measurements (length of body, hind femur and tibia, cerci and weight) and Body Condition Index were taken from males. Study species prefers mesophilous montane up to alpine meadows in higher elevations (over 600 m a.s.l.). The development started over one month earlier in lowlands and populations reached several fold higher density there. Males from lowlands had body parameters significantly bigger apart from cerci. Cerci were significantly longer in males from mountains. However, males of the same size were significantly heavier in higher altitudes. In conclusion, refuges of montane meadows ecosystem support species survival nowadays.